(untitled) (Research, Society and Development, 2021)
Pterodon pubescens is a native species, popularly known as “faveiro”, “sucupira-branca”, “fava-de-sucupira”, “sucupira”, and “sucupira-lisa”, belonging to the family Leguminosae-Papilionoideae (Fabaceae). This study aimed to analyze the effect of different treatments on the breaking of seed dormancy in Pterodon pubescens (Leguminosae, Papilionoideae). The seeds were collected in four places in the municipality of Cáceres (Mato Grosso, Brazil). They were selected by flotation or deposition in a container with water, washed with sodium hypochlorite (2% active chlorine), and subjected to five treatments, as follow: (T1) control, (T2) seeds had their woody integument removed and were washed with detergent; (T3) seeds were scarified and immersed in a container containing 500 ml of cola-based soft drink, for an hour and a half; (T4) seeds had only their integument removed; and (T5) seeds were subjected to scarification, using a file, until the embryo was visible. T2 and T4 were the most effective treatments for the emergence of P. pubescens seed.